Experimental Studies on Bio-Bitumen Produced Using Charcoal from Coconut Shell Waste - Garg, Nishant (My University, 2019)
Road network plays important role in transportation to carry passengers and goods from one place to another. It is the basic need for development of infrastructure, helps in increasing socio-economic standards and economic growth of country. Pavement should be designed such that it can be capable to bear heavy loads in extreme environment conditions, undergo less wear and tear, good riding quality and drainage to prevent from moisture damage. Most of the Indian roads are of flexible pavements and the main distresses occur in the pavements are rutting and fatigue cracking which affects the serviceability and durability of the pavement. Although bitumen is only 5- 6% by weight of mixture, it has 40% effect on the performance during service life. With the increase in percentage of over-loaded commercial vehicles, premature rutting in the bituminous mixtures has been observed very often on pavements and which leads to increase the maintenance cost of road network. So modification of binder is necessary now days. In order to stiffen the bitumen, several methodologies have been adopted in the past and still research is being carried out in various other aspects to produce bitumen with superior permanent deformation resistance i.e. modified bitumen. On the other hand, tropical countries such as Indonesia, India, Philippines, and Srilanka being one of the largest producers of coconut in the world also produce burnt coconut shell (CS) waste, which creates environmental concern regarding disposal due to large percentage of carbon. The main objective of this study was to reduce the environmental waste and use the charcoal powder from the CS waste as additive to VG30 bitumen at 0, 1, 2, 3 and 4% (by wt. of bitumen) and investigate its permanent deformation characteristics. The size of the MCP is less than 75 μ. High shear mixture at 1720 rpm at 150°C for 60 min was used to mix the MCP into bitumen. The basic properties of bitumen such as penetration value, softening point, penetration index were determined to understand the consistency of the bitumen. Further, dynamic shear rheometer (DSR) was used to determine rutting parameter (|G*|/sinδ), complex modulus (G*) phase angle (δ), loss factor (tanδ) and more other parameters. The permanent deformation resistance of bitumen was studied using multiple stress creep recovery (MSCR) test to quantify creep compliance, %recovery, and stress sensitivity. Frequency and temperature vi sweep test was also done to see the loading time. Moreover SPSS software was used for statistical analysis and scanning electron microscope test was conducted at MCP and modified binder to see the dispersion and homogenous mix of modified bitumen. The results showed that addition of MCP into neat binder has significantly increased the properties of control binder. Modified binder increases the rutting performance, stiffness of binder, creep recovery, elastic properties and makes the binder less sensitive at 2% addition of MCP.
ME Thesis
Keywords: Modified bio-bitumen; Microcharcoal Particles; coconut shell waste; Rheology and rutting parameter